Numerical Simulation Method for Tunnel Excavation Considering Mechanical Characteristic Variation of Soft Rock with the Confining Pressure Influence - Yucang Dong; Hai Zhang; Zhengguo Zhu; Yongquan Zhu (Applied Sciences, 2023)
The accurate prediction and evaluation of stress and displacement fields of surrounding rock is the fundamental premise for the deformation control of soft rock tunnels under high geo-stress condition. However, due to the complicated mechanical characteristics of soft rock with confining pressure influence, the current numerical simulation method usually regards the mechanical parameters of surrounding rock as constant and ignores the variation of these parameters in the simulation process, which leads to results that cannot accurately reflect the mechanical behavior of surrounding rock. Therefore, this paper firstly investigates the effect of confining pressure on deformation and strength parameters for soft rock and proposes corresponding variable models for mechanical parameters with the confining pressure influence. Secondly, a transversal loop discriminant update procedure is proposed and introduced into the iteration calculation process of FLAC3D, thus forming an improved numerical simulation method. This improved method can integrally consider the mechanical parameter variation of surrounding rock with variable confining pressure and realize the automatic update for such a parameter with its variable stress state. Finally, as an application example, an improved expression of longitudinal deformation profile (LDP) for tunnels considering the confining pressure influence is proposed based on numerous simulation results for a soft rock tunnel obtained by this proposed method.